Parents' Postnatal Sense of Security: A Concept Analysis - Tieying Zeng; Lingjun Jiang; Deqing Huang; Meiliyang Wu; Aiqing Tu (Nursing Open)
ABSTRACT Aim Parents' postnatal sense of security is often mentioned in recent publications, but there is no consensus on its definitions and measurement. A concept analysis was conducted to clarify the definition, the attributes, antecedents and the consequences of parents' postnatal sense of security and to promote consistency in its usage. Design Walker and Avant's eight‐step concept analysis model was adopted to define the concept of parents' postnatal sense of security. Methods A comprehensive search of multiple databases (Sinomed, CNKI, Wanfang database, CINAHL, PubMed, Embase, Web of Science, ProQuest, PsyInfo and Cochrane Library) was conducted to identify relevant articles from the inception of the databases until December 2022. In addition, a manual search was performed to gather any additional papers related to the topic. Ultimately, a total of 48 articles were included in the concept analysis. Results Three attributes were identified: perceive one's physical well‐being not being threatened, feel confident and in control of the parenting role, feel confident in one's available relationships. The identified antecedents were: being prepared for child rearing, being in familiar or safe environment, general well‐being of the baby and parents, support from medical staff and family members, being empowered by medical staff. Consequences of parents' postnatal sense of security included successful adaptation to the parental role, decreased postpartum depression symptoms in mothers, successful infant care and the development of parent‐infant relationship.